Effect of Curvularia andropogonis infection on secretory tissues and phenylalanine ammonia lyase enzyme of Cymbopogon nardus - ROFIATUN SOLEKHA; NI N. T. PUSPANINGRUM; AISYAH H. RAMADANI; FEBIANTI D. HAPSARI; DINI ERMAVITALINI; HERY PURNOBASUKI (Society for Indonesian Biodiversity, 2024)
Abstract. Solekha R, Puspaningrum NNT, Ramadani AH, Hapsari FD, Ermavitalini D, Purnobasuki H. 2024. Effect of Curvularia andropogonis infection on secretory tissues and phenylalanine ammonia lyase enzyme of Cymbopogon nardus. Biodiversitas 25: 598-604. Cymbopogon nardus L. oil production decreased due to red spot disease caused by Curvularia andropogonis fungal infection. The objective of this study was to investigate the infection effect of C. andropogonis on secretory tissue formation in citronella leaf epidermis and the enzymatic defense expression response in C. nardus. Anatomical responses were observed from leaf secretory structure slide while PAL reactions were measured from enzyme activity in leaf samples of three treatment groups with healthy, wounded, and infected conditions. The morphological results of infected leaves changed from green to brownish triggered by pathogenic infection conditions that activated the PAL enzyme pathway and phenylpropanoid production as a defense. The results showed that the density of cells storing secondary metabolites flavonoids, tannins, and saponins in infected leaves increased compared to wounded and healthy ones. Secondary metabolites flavonoids, tannins, and saponins in wounded leaves increased compared to healthy leaves. It was observed that enzymatic response escalated when infection occurred. PAL enzyme activity test of C. nardus leaves showed that infected leaves had the highest value (0.0051 U/mL), followed by wounded leaves (0.0033 U/mL) and healthy leaves (0.0027 U/mL). Likewise, the specific activity of PAL enzyme in infected leaves was highest (0.121 U/mg), followed by injured leaves (0.040 U/mg) and healthy leaves (0.022 U/mg). The overall results exhibited that C. andropogonis infection affects the quality of secretory tissue and increases PAL enzyme activity as a form of defense. By detecting secretory tissue and defense enzymes after infection, further research can be carried out regarding controlling Curvularia andropogonis infections by engineering enzymes and secondary metabolites.